Authoritarian Innovations: Crafting support for a less democratic Southeast Asia. Issue 6 (17th August 2020) - Curato, Nicole; Fossati, Diego
ABSTRACT: Contemporary democratic backsliding typically unfolds gradually, as elected incumbents slowly and relentlessly subvert democratic institutions without openly questioning the principles of democracy. This suggests that more attention should be devoted to studying the new practices through which authoritarian actors undermine democratic institutions and mobilize consensus for their agendas. In focusing on authoritarian practice, this Thematic Collection emphasizes the dynamism, the fluidity and the transformative potential of various sophisticated tactics employed by authoritarians to stifle opposing voices, demobilize dissent and erode the foundations of representative democracy. We name such practices "authoritarian innovations", and we study them in the context of Southeast Asia, a region that has provided several examples of democratic erosions in recent years. Contributions in this thematic section offer an overview of trends of regime change in the region, as well as studies of authoritarian innovations in Indonesia, Malaysia, and Singapore. These cases indicate the urgency of focusing on various actors who may collude with authoritarians in the state to assail spaces of democratic contestation and participation, and on the various context-specific practices that they skillfully implement.